Differences in strength and landing biomechanics between female jumpers and swimmers - Ruan, Mianfang; Zhang, Qiang; Zhang, Xin; Hu, Jing; Wu, Xie (Isokinetics and exercise science, 2022)
BACKGROUND: It remains unclear if plyometric training as a single component could improve landing mechanics that are potentially associated with lower risk of ACL injury in the long term OBJECTIVE: The purpose of this study was to investigate the influence of experience undertaking plyometrics on landing biomechanics in female athletes. METHODS: Non-jumpers with little experience in plyometric training (12 female college swimmers) and jumpers with five years of experience in plyometric training (12 female college long jumpers and high jumpers) were recruited to participate in two testing sessions: an isokinetic muscle force test for the dominant leg at 120 ∘ /s and a 40-cm drop landing test. An independent t test was applied to detect any significant effects between cohorts for selected muscle force, kinematic, kinetic, and electromyography variables. RESULTS: While female jumpers exhibited greater quadriceps eccentric strength ( P = 0.013) and hamstring concentric strength ( P = 0.023) during isokinetic testing than female swimmers, no significant differences were observed in kinematics, kinetics, and muscle activities during both drop landing and drop jumping. CONCLUSIONS: The results suggest that the female jumpers did not present any training-induced modification in landing mechanics regarding reducing injury risks compared with the swimmers. The current study revealed that plyometric training as a single component may not guarantee the development of low-risk landing mechanics for young female athletes.